Comparison of Sodium-And Sulfate-Based Activators for the Sustainable Development of Hybrid Alkaline Fly Ash Pastes with High so 4 Content - Brescia-Noranmbuena, L (American Society of Civil Engineers, 2025)
Hybrid alkaline fly ash pastes (HAFAPs) aim to maximize the fly ash (FA) content to reduce environmental impact and cost. However, significant amounts of FAs are discarded because they have high SO4 content. These FAs have been described as stable in HAFAPs when sodium alkaline activators are used, but sulfate-based activators have not been studied. Therefore, this research assesses the effect of different activators on HAFAPs formulated with high SO4, evaluating compressive strength and sulfate resistance. The results showed that high-SO4 FAs demonstrated a higher strength than low-SO4 FAs, with sodium-based activators being more susceptible to the binder/activator ratio and presenting a lower strength in high-SO4 HAFAPs. On the other hand, sulfate-based activators presented a higher strength but were unstable to external sulfate attack. Therefore, even though high-SO4 FAs have been described as stable to internal sulfate attack when sodium activators are used, external sulfates severely affect the durability of HAFAPs, so they are not recommended as construction material. © 2025 American Society of Civil Engineers.